The Influence of Self-Efficacy and Love of Work on Teacher Work Engagement in the Frontier, Outermost, Disadvantaged (3T) Regions of Sanggau Regency, West Kalimantan - Aulia, Aulia; Hamidah, Annisaul; Danastri, Ajeng Dwi Retno Ambar (Journal of Educational, Health and Community Psychology, 2024)
It is assumed that the great challenges and responsibilities at work can affect the work engagement of teachers who teach in the 3T (Frontier, Outermost, Disadvantaged) areas of Sanggau Regency, West Kalimantan. This research aims to examine the influence of self-efficacy and love of work on teacher work engagement in the 3T area. The method in this research uses the correlation method. The population used in this research were teachers who taught in the 3T area of Sanggau Regency, West Kalimantan, both in public and private elementary, middle, high school or vocational school, and had worked for at least one year. This research uses a proportional stratified sampling technique to determine the sample. The instruments used to collect data used the modified Utrecht Work Engagement Scale (UWES), self-efficacy scale, and love of work scale. Based on data processing using multiple linear regression analysis, it shows that the coefficient R=0.644, F=151.449 (p<0.01), so it can be concluded that simultaneously self-efficacy and love of work have an influence on teacher work engagement in the 3T area of Sanggau Regency, West Kalimantan.